Empirical Investigation of the Environmental Kuznets Curve Hypothesis for Nitrous Oxide Emissions for Mongolia - Och, Maralgua (International Journal of Energy Economics and Policy, 2017)
A comprehensive set of econometric methods were employed on annual data from 1981-2012 to investigate the environmental Kuznets curve hypothesis for nitrous oxide emissions for Mongolia; the short- and long-run relationships between nitrous oxide emissions, income, exports, urbanization, and growth in the different sectors of the economy; and their consequent Granger causal relationships. A highly significant and robust long-run U-shaped relationship between nitrous oxide emissions and income was found; thereby, discrediting the existence of the environmental Kuznets curve. Furthermore, exports, urbanization, and growth in the industrial and services sectors were found to decrease - while growth in the agricultural sector was found to increase - nitrous oxide emissions. Finally, the findings have also exhibited significant short- and long-run Granger causal relationships amongst the variables; thereby, leading to policy recommendations which are briefly discussed. Keywords: Mongolia, environmental Kuznets curve hypothesis, nitrous oxide emissions JEL Classifications: C32, O13, O53, Q53, Q56